THE EFFECT OF MANAGERIAL OWNERSHIP, PROFITABILITY AND INVESTMENT OPPORTUNITY SET ON CASH DIVIDENDS WITH LIQUIDITY AS MODERATING VARIABLES - Moch. Topal Wildan (Jurnal Proaksi, 2021)
This study aims to determine the impact of managerial ownership, profitability, investment opportunity sets on cash dividends with liquidity as a moderating variable. The data in this study were obtained from the Indonesia Stock Exchange website. This type of research is qualitative research. The sampling technique in this study was purposive sampling with several criteria for food and beverage sub-sector companies for four consecutive years resulting in 18 companies. The analysis model used is moderated regression analysis (MRA). The results of this study indicate that managerial ownership and investment opportunity sets do not affect cash dividends. In contrast, profitability does affect cash dividends, and liquidity does not moderate managerial ownership, profitability and investment opportunity sets.